Lily Boop - Switzer, Ellen Eichenwald (New York : Crown Publishers, 1986)
A young girl describes her adventures with her unusual friend, Lily Boop, who keeps a pet slug and eats raw eggs for lunch.
3.6
K-3
K-3
School Library Journal
Keywords: Friendship -- Fiction; Friendship -- Fiction